Lentera model a mixed-methods validation of a hybrid framework for circular waste governance in Bali tourism destination - Darmayasa, I Ketut; Mudana, I Gede; Oka, I Made Darma; Astawa, I Putu (Technium Social Sciences Journal, 2026)
This study aims to validate LENTERA model as a comprehensive framework for advancing circular waste governance in tourism destinations (Purpose). The LENTERA construct comprising Local Knowledge, Education, Networking, Technology, Environmental Care, Reduce of Waste, and Action is conceptualized as a set of dynamic capabilities that enable Circular Economy Adoption and strengthen Sustainable Tourism Governance. Despite growing attention to circularity in tourism, empirical evidence that integrates cultural embeddedness, technological adoption, and governance mechanisms remains limited, indicating a research gap addressed in this study. A sequential explanatory mixed-methods design was applied. The quantitative phase surveyed 100 tourism stakeholders and employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess reliability, predictive relationships, and effect sizes among the LENTERA constructs. The qualitative phase included 28 in-depth interviews and two focus group discussions to contextualize and explain the statistical outcomes. The findings indicate that all seven LENTERA pillars significantly influence Circular Economy Adoption (R² = 0.64), which strongly predicts Sustainable Tourism Governance outcomes (R² = 0.48). Waste reduction, action mechanisms, and technology demonstrated the strongest predictive power and represent critical leverage points for system transformation. Qualitative insights further reveal that cultural legitimacy rooted in indigenous values such as Tri Hita Karana enhances stakeholder acceptance and operational compliance. This study provides theoretical advancement and a validated decision-support tool for policymakers, tourism operators, and destination managers seeking to transition toward circular tourism systems.